Dynamical ejecta synchrotron emission as a possible contributor to the changing behaviour of GRB170817A afterglow. Issue 4 (27th July 2021) - Nedora, Vsevolod; Radice, David; Bernuzzi, Sebastiano; Perego, Albino; Daszuta, Boris; Endrizzi, Andrea; Prakash, Aviral; Schianchi, Federico
ABSTRACT: Over the past 3 yr, the fading non-thermal emission from the GW170817 remained generally consistent with the afterglow powered by synchrotron radiation produced by the interaction of the structured jet with the ambient medium. Recent observations by Hajela et al. indicate the change in temporal and spectral behaviour in the X-ray band. We show that the new observations are compatible with the emergence of a new component due to non-thermal emission from the fast tail of the dynamical ejecta of ab-initio binary neutron star merger simulations. This provides a new avenue to constrain binary parameters. Specifically, we find that equal mass models with soft equations of state (EOSs) and high-mass ratio models with stiff EOSs are disfavoured as they typically predict afterglows that peak too early to explain the recent observations. Moderate stiffness and mass ratio models, instead, tend to be in good overall agreement with the data.